Emerging Targeted Strategies in Advanced Hepatocellular Carcinoma - Finn, Richard S. (Seminars in Liver Disease, 2013)
Treatment of advanced-stage hepatocellular carcinoma (HCC) remains a challenge because of the complex nature of the disease and the lack of available therapies. The antiangiogenic multikinase inhibitor sorafenib is the first therapy to demonstrate a significant overall survival benefit in advanced HCC. However, new agents for both first- and second-line treatment of advanced HCC are needed. The multiple pathways involved in HCC oncogenesis, proliferation, and survival provide many opportunities for the development of molecularly targeted therapies. Many novel agents are under investigation in phase III trials in advanced HCC, including antiangiogenic multikinase inhibitors (e.g., brivanib, sunitinib, linifanib) and inhibitors of the mammalian target of rapamycin (mTOR) pathway (e.g., everolimus). Although these therapies have demonstrated some utility as single agents in advanced HCC, rational combinations of therapies are likely to provide greater success. Current research efforts are directed at combining agents targeting different molecular pathways (e.g., sorafenib in combination with erlotinib) and combining molecularly targeted agents with systemic chemotherapy or transarterial chemoembolization (TACE). Therapies targeting other molecular pathways in HCC are in early development; future research will focus on discovering additional targets for therapy and identifying biomarkers that predict the success of current therapies.
Keywords: hepatocellular carcinoma; brivanib; angiogenesis inhibition; mTOR inhibition; combination therapy